Visualizing childhood in Upper Palaeolithic societies: Experimental and archaeological approach to artists' age estimation through cave art hand stencils. (April 2022) - Fernández-Navarro, Verónica; Camarós, Edgard; Garate, Diego
Abstract: This paper presents rock art as a collective action in which different strata of society took part, including children and subadults. Until recent decades archaeology of childhood has not been in the main focus of the archaeological research, much less the participation of those children in the artistic activity. The present study approaches the palaeodemography of artists in the decorated caves through the paleolithic rock art itself. The approximate age of these individuals has been calculated through the biometric analysis of hand stencils in the caves of Fuente del Salín, Castillo, La Garma, Maltravieso and Fuente del Trucho, using 3D photogrammetric models as reference. The results have been compared with a modern reference population in order to assign the Palaeolithic hands to certain age groups. It has been demonstrated the presence of hand stencil motifs belongs to infants, children and juveniles, revealing this stratum's importance in the artistic activity. Highlights: Palaeolithic hand stencils corpus is formed by over 750 representations distributed in France, UK, Spain and Italy. Palaeolithic hand stencils are a primary source of information for the characterisation of the prehistoric population. Our morphometrical hand study suggest infants, children and juveniles' participation in graphic production. This result presents rock art as a collective action in which different strata of society took part.